2023
DOI: 10.1088/1361-6463/acc259
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of atmospheric pressure helium plasma jet with tilted dielectric target: split and deviation of ionization waves

Abstract: Atmospheric pressure plasma jets (APPJs) are commonly used plasma sources in many biomedical applications. Typically, the APPJs are not always perpendicular to the target to be treated. In this paper, the effects of tilted angle (α), relative permittivity (εr) of the target, the target potential, the distance (d) and the discharge parameters on the interaction of a helium APPJ with the target are investigated. Spatio-temporal resolved images show that the ionization wave (IW) split into a surface ionization wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…Second, the mismatch between the IW propagation direction and the enhanced electric field direction, which occurs as a result of the APPJ tilt. The details of the IWs split are discussed in our previously published work [52]. It is observed that the intensity of the IW corresponding to the falling edge of the pulse is much lower than the IW generated by the rising edge, and the SIW formed by IW cannot propagate along the surface.…”
Section: Dynamic Distribution Of Surface Electric Field Under Plasma ...mentioning
confidence: 92%
See 1 more Smart Citation
“…Second, the mismatch between the IW propagation direction and the enhanced electric field direction, which occurs as a result of the APPJ tilt. The details of the IWs split are discussed in our previously published work [52]. It is observed that the intensity of the IW corresponding to the falling edge of the pulse is much lower than the IW generated by the rising edge, and the SIW formed by IW cannot propagate along the surface.…”
Section: Dynamic Distribution Of Surface Electric Field Under Plasma ...mentioning
confidence: 92%
“…The two impact points shown in the surface electric field are caused by the IW splitting above the dielectric. This phenomenon occurs due to a combination of the electric field enhancement caused by dielectric polarization effect and the mismatch of the IW propagation direction [52]. The SIW then propagates along the surface, forming an extended region to the right of the spot.…”
Section: Dynamic Distribution Of Surface Electric Field Under Plasma ...mentioning
confidence: 99%